The Antioxidant Effect of Dietary Bioactives Arises from the Interplay between the Physiology of the Host and the Gut Microbiota: Involvement of Short-Chain Fatty Acids - Rossana Cuciniello; Francesco Di Meo; Stefania Filosa; Stefania Crispi; Paolo Bergamo (MDPI AG, 2023)
The maintenance of redox homeostasis is associated with a healthy status while the disruption of this mechanism leads to the development of various pathological conditions. Bioactive molecules such as carbohydrates accessible to the microbiota (MACs), polyphenols, and polyunsaturated fatty acids (PUFAs) are food components best characterized for their beneficial effect on human health. In particular, increasing evidence suggests that their antioxidant ability is involved in the prevention of several human diseases. Some experimental data indicate that the activation of the nuclear factor 2-related erythroid 2 (Nrf2) pathway-the key mechanism in the maintenance of redox homeostasis-is involved in the beneficial effects exerted by the intake of PUFAs and polyphenols. However, it is known that the latter must be metabolized before becoming active and that the intestinal microbiota play a key role in the biotransformation of some ingested food components. In addition, recent studies, indicating the efficacy of the MACs, polyphenols, and PUFAs in increasing the microbial population with the ability to yield biologically active metabolites (e.g., polyphenol metabolites, short-chain fatty acids (SCFAs)), support the hypothesis that these factors are responsible for the antioxidant action on the physiology of the host. The underlying mechanisms through which MACs, polyphenols, and PUFAs might influence the redox status have not been fully elucidated, but based on the efficacy of SCFAs as Nrf2 activators, their contribution to the antioxidant efficacy of dietary bioactives cannot be excluded. In this review, we aimed to summarize the main mechanisms through which MACs, polyphenols, and PUFAs can modulate the host's redox homeostasis through their ability to directly or indirectly activate the Nrf2 pathway. We discuss their probiotic effects and the role played by the alteration of the metabolism/composition of the gut microbiota in the generation of potential Nrf2-ligands (e.g., SCFAs) in the host's redox homeostasis.